Development of textile fibers from the bacterial cellulose of acetobacter xylinum and a aomparative analysis of their physical properties - Manding, Abubakar M.
The increased consumption of basic human necessities, such as food and clothing, comes with the heightened accumulation of waste. Developing a technology that uses food waste to produce textile materials can address this issue. This study is based on the research conducted by Canals (2014), in which a textile was developed from the bacterial cellulose (BC) of Acetobacter xylinum. To further the mentioned research, this study employed an experimental design divided into three phases: production of textile fibers from the BC of Acetobacter xylinum by fermenting coconut water in three different incubation periods; determination of physical properties of the BC fibers, specifically their tensile strength, elongation and fiber fineness; and comparative analysis of the properties of the experimental group using One-way ANOVA, and against polyester using One-sample T-test statistical analysis. The results showed that the incubation period of the culture affects the physical properties of BC fibers. Batch B, with a 2-week incubation period, had the most favorable properties in the experimental group. However, when compared to polyester, the properties of the BC fibers are significantly less. Further research needs to be pursued on how to enhance the physical properties of the BC fibers. It can be through experimentation using other food wastes with higher carbon content, and improvement of the methodology in developing and treating BC. The researcher suggests mechanization when cutting and turning BC films into fibers. The application of the BC fibers developed in this study, with regard to their physical properties, can also be explored.